2022
DOI: 10.3389/fneur.2022.826734
|View full text |Cite
|
Sign up to set email alerts
|

A Decentralized ComBat Algorithm and Applications to Functional Network Connectivity

Abstract: Recent studies showed that working with neuroimage data collected from different research facilities or locations may incur additional source dependency, affecting the overall statistical power. This problem can be mitigated with data harmonization approaches. Recently, the ComBat method has become commonly adopted for various neuroimage modalities. While open neuroimaging datasets are becoming more common, a substantial amount of data is still unable to be shared for various reasons. In addition, current appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This model has also been extended to unique data settings, such as those where covariate effects are non-linear, longitudinal data is present, decentralized learning is required, multiple batch variables should be corrected for, or traveling subjects are available (Bayer et al, 2022;Bostami et al, 2022;Chen et al, 2022b;Horng et al, 2022;Maikusa et al, 2021;Pomponio et al, 2020). In applied studies, ComBat-family methods have been widely used and shown to improve inference and generalizability of results (Acquitter et al, 2022;Bartlett et al, 2018;Bourbonne et al, 2021;Crombé et al, 2020;Fortin et al, 2018;Marek et al, 2019;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This model has also been extended to unique data settings, such as those where covariate effects are non-linear, longitudinal data is present, decentralized learning is required, multiple batch variables should be corrected for, or traveling subjects are available (Bayer et al, 2022;Bostami et al, 2022;Chen et al, 2022b;Horng et al, 2022;Maikusa et al, 2021;Pomponio et al, 2020). In applied studies, ComBat-family methods have been widely used and shown to improve inference and generalizability of results (Acquitter et al, 2022;Bartlett et al, 2018;Bourbonne et al, 2021;Crombé et al, 2020;Fortin et al, 2018;Marek et al, 2019;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%